﻿Geographic variation in body size of the migratory locust Locusta migratoria (Orthoptera, Acrididae): Masaki’s cline and phase polyphenism - Seiji Tanaka (Journal of Orthoptera Research, 2024)
Adults of the migratory locust Locusta migratoria (Linnaeus, 1758) were collected in the Japanese Archipelago, which extends from the Ryukyu subtropical region to the Hokkaido cool-temperate region, covering more than 2,500 km. A saw-toothed pattern was observed in body size along the latitudinal or annual mean temperature gradient, which is similar to Masaki’s clines initially described for crickets. The latitudinal cline of locusts was also observed in the laboratory, suggesting that this cline was primarily due to genetic variation. In the northern univoltine zone, locust body size increased toward the south. The latitudinal size trend was reversed in the transitional zones where the voltinism shifted from univoltine to bivoltine and from bivoltine to trivoltine life cycles. These patterns may be explained by changes in the length of the growing season for development and reproduction. Body size varied with growth efficiency but not with the variable lengths of nymphal development. Larger females had more ovarioles and produced fatter egg pods containing more eggs per pod. The morphometric ratio, F/C (hind femur length/head width), tended to decrease with latitude, but this characteristic could be primarily due to phylogenetic differences between the northern and southern clades. It was confirmed that F/C ratio decreased when the locusts were reared in a group. The sexual size dimorphism, or SSD, tended to increase as the mean body sizes of populations increased, converse to Rensch’s rule. The relative body size of females and males correlated with latitude and was greatly reduced when the insects were reared in a group. The smaller rate of increase at higher latitudes may be related to male–female associations and predation pressure.